2012
DOI: 10.5688/ajpe767131
|View full text |Cite
|
Sign up to set email alerts
|

An Online Virtual-Patient Program to Teach Pharmacists and Pharmacy Students How to Provide Diabetes-Specific Medication Therapy Management

Abstract: Objective. To develop, implement, and assess the effectiveness of an online medication therapy management (MTM) program to train pharmacists and pharmacy students in providing MTM services for patients with diabetes and to increase their intent to perform these services.Design. An online program was created using an Internet-based learning platform to simulate 4 MTM meetings between a pharmacist and a virtual patient diagnosed with diabetes. Assessment. Eighty students and 42 pharmacists completed the program.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 15 publications
0
54
0
1
Order By: Relevance
“…Every study assessed a different learning topic, although 3 studies included diabetes within their focus. [30][31][32] Six studies (35%) assessed effectiveness of e-learning in pharmacists; [32][33][34][35][36][37] 10 studies (59%) assessed pharmacy students (of which 1 included preregistration pharmacists), 31,[38][39][40][41][42][43][44][45][46] and 1 study assessed both pharmacists and pharmacy students. 30 The number of participants in each study ranged from .…”
Section: Resultsmentioning
confidence: 99%
“…Every study assessed a different learning topic, although 3 studies included diabetes within their focus. [30][31][32] Six studies (35%) assessed effectiveness of e-learning in pharmacists; [32][33][34][35][36][37] 10 studies (59%) assessed pharmacy students (of which 1 included preregistration pharmacists), 31,[38][39][40][41][42][43][44][45][46] and 1 study assessed both pharmacists and pharmacy students. 30 The number of participants in each study ranged from .…”
Section: Resultsmentioning
confidence: 99%
“…10 To date, the literature describing curricular implementation of MTM skills mostly surrounds elective and experiential courses. [11][12][13][14][15][16] In fact, the literature lacks a description of a core course designed to emphasize MTM core elements as skill content across settings in which a pharmacist may perform MTM services. Based on accreditation requirements, it may be assumed that the concepts and skills necessary to adequately perform MTM are spread throughout the entirely of pharmacy curricula.…”
Section: Introductionmentioning
confidence: 99%
“…4,[6][7][8][9][10][11][12][13][14][15][16] Despite a lack of comparison of virtual scenarios to an alternative method of learning, virtual patient scenarios are innovative, realistic, and engaging learning activities by student report and improve student didactic knowledge. 4,7,[9][10][11][12][13][14] Benedict and colleagues surveyed students at the conclusion of a therapeutics course that had implemented patient scenario simulations to augment traditional lectures and found that students either agreed or strongly agreed the simulations were enjoyable (92%), stimulated interest in course content (82%), and should be further incorporated into the curriculum (86%). 12 In a disease state management course, Douglas et al assessed the impact of virtual patient case scenarios on pharmacy student clinical competence skills through administration of four short-answer questions before and after exposure to patient case simulations.…”
Section: Introductionmentioning
confidence: 99%